2021
DOI: 10.17977/um065v1i82021p660-664
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Miskonsepsi Materi Sistem Peredaran Darah Manusia Tema 4 pada Siswa Kelas V SD

Abstract: This study aims to describe the material misconceptions about the human circulatory system in fifth grade students at SD Negeri 1 Sumberpasir. This study uses a qualitative approach with data collection through essay tests and interviews. The research subjects were fifth grade students. The results showed that there were still many students who had misconceptions about the concept of the human circulatory organ, the process of human blood circulation, human blood circulation disorders and how to maintain the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Material studies carried out on the circulatory system show that the material for the circulatory system has a broad and more in-depth coverage of material compared to the material for the respiratory system. In addition, in the material of the circulatory system there are still a lot of misconceptions when compared to misconceptions that occur in the respiratory system (Rohmadhani et al, 2021;Bordes et al, 2020;Vitharana, 2021;Izza et al, 2021). The results of research conducted by Khairaty et al (2018) explained that the findings of many misconceptions in the circulation system material were caused by the lack of student interest in the lesson, the number of scientific terms encountered, the tendency of students who were accustomed to memorizing, teacher-centered learning, there was no teacher confirmation to students about concepts that were lacking.…”
Section: Resultsmentioning
confidence: 99%
“…Material studies carried out on the circulatory system show that the material for the circulatory system has a broad and more in-depth coverage of material compared to the material for the respiratory system. In addition, in the material of the circulatory system there are still a lot of misconceptions when compared to misconceptions that occur in the respiratory system (Rohmadhani et al, 2021;Bordes et al, 2020;Vitharana, 2021;Izza et al, 2021). The results of research conducted by Khairaty et al (2018) explained that the findings of many misconceptions in the circulation system material were caused by the lack of student interest in the lesson, the number of scientific terms encountered, the tendency of students who were accustomed to memorizing, teacher-centered learning, there was no teacher confirmation to students about concepts that were lacking.…”
Section: Resultsmentioning
confidence: 99%
“…Research according to Izza et al (2021) confirms that there are still many students who have human heart problems in terms of mental health, social health, social and blood circulation and so on. In addition, the same problem can be observed in a study of Negoro et al (2018) which showed that the understanding of learners increases and misconceptions decrease.…”
Section: Introductionmentioning
confidence: 99%